Penanaman Nilai Etika Kristiani terhadap Anak Peneladanan Karakter - Josefin Harianja; Aritonang Situmeang; Diana Martiani Situmeang (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2025)
Christian religioun education regarding values ​​and ethics must be able to guide and develop the character and ethical values ​​according to what is taught in the Bible, for students at school have the right foundation from an early age. The method used is an analytical method that analyzes problems using qualitative methods with a study approach. This research relates to data or written material that is appropriate to the topic of discussion. Christ's character education method given to children is not just theoretical, but as parents directly and automatically become teachers who must teach noble values ​​in the family and provide and share role models for children to emulate. Character education is a system of instilling and developing character values ​​in children which includes knowledge, awareness or will, and actions to implement these values, both towards God, oneself, others, the environment and nationality so that they become virtuous human beings.